The evolution of the dragon in China: A discourse analysis perspective - Srisinthon, Pairin; Chayanuvatr, Anchalee (Research Journal in Advanced Humanities, 2025)
This article examines the historical narrative of the mythical dragon in China from ancient times to the present.  This process is explained with Foucault’s Concept of “Power” and Fairclough’s “Critical Discourse Analysis”. Examining the extensive process that produces the “Dragon” discourse reveals the implications of discourse practices and the artfulness of people in power who create knowledge and truth related to the dragon. It can be concluded that the reasons for producing the dragon discourse are to strengthen the rulers’ power and establish order in society. The ancient discourse of the dragon deity is linked to the righteous “leadership” entrusted to the rulers in the feudal era of China. Thus, reproducing the discourse “descendants of the dragon” has become easily acceptable from the past to the modern era to give the Chinese a sense of belonging, commitment, and pride in their nation.  The significant correlation between the mass media, state-owned media, and political institutions in China plays a pivotal role in conveying the dragon discourse in the current context.